Flora fóssil do pontal Rip, Ilha Nelson, Península Antártica: taxonomia e contexto geológico - Bastos, Bibiana Liguori (Universidade do Vale do Rio dos Sinos, 2012)
Plant fossils are common in the Antarctic Peninsula and have been found not only in the eastern areas that correspond to the back arc deposition environments, but also in the Graham Land and the South Shetland archipelago, which represent the arc and fore arc contexts, respectively. In the Nelson Island, part of the South Shetland archipelago, the fóssil record is deeply linked to the volcanic processes that marks its geological history, initially affected by the Mesozoic subduccion events and after by the construction of an island arc. The macro and microflora found in a reworked pyroclastic deposit from the upper part of Rip Point outcrop, in northwestern Nelson Island, are herein presented for the first time. The macroflora is dominated by very fragmented leaves of Nothofagus and primitive forms of angiosperms, related to the families Lauraceae, Anacardiaceae and Melastomataceae. Rare pinnules of Pteridophyta and a sole and partial conifer shoot also compound this assemblage. Amongst the palynomorphs, the Pteridophyta are a main component, follow by pollen grains of gymnosperms. The presence of grains related to Nothofagus is represented by ancestral and modern types (e.g. Nothofagidites cf. endurus, N. cf. kaitangataensis and N. cf. brachyspinulosus). The Classopollis grains, in association with Nothofagidites cf. endurus, N. cf. kaitangataensis, suggested a Late Cretaceous age to this deposit. In relation to stratigraphic correlation, the composition of macroflora showed also a greatest identity with ones recorded in other exposures found in the King George Island, specially, with assemblages attributed to the middle Campanian (e.g. Half Three point, Price point and Zamek Hill). In terms of paleophytogeography, it was possible observe the domain of angiosperms related to a deciduous and primitive leaves of Nothofagus, similar to many of modern species that live in southern South America. In this way, it is suggested that the Antarctic Peninsula was under a humid temperate climatic condition during the deposition time of study interval, based on the domain of microfilic leaves and the presence of leaves and pollen grains related to Nothofagus. Finally, it should be highlighted that the pteridophytes (families Blechnaceae e Hymenophyllaceae), the cupressacea of genus Papuacedrus and the few morphotypes associated to Nothofagus described here, indicated the existence of a land connection between the Antarctic Peninsula and Australasia during the end of Cretaceous.
Keywords: Tafoflora; Nothofagus; Ilha Nelson; Península Antártica; Cretáceo Superior; Taphoflora; Nelson Island; Antarctic Peninsula; Upper Cretaceous; ACCNPQ::Ciências Exatas e da Terra::Geologia